Comparison of two perioperative antibiotic schedules in patients undergoing surgical reconstruction with dermal matrix after excision of skin cancer. Issue 4 (30th March 2020) - Fiorentini, Chiara; Bedini, Andrea; Mandel, Victor Desmond; Bacca, Erica; Menozzi, Marianna; Reggiani, Camilla; De Pace, Barbara; Meschiari, Marianna; Santoro, Antonella; Franceschini, Erica; Mussini, Cristina; Terrenato, Irene; et al.
Abstract: Perioperative antibiotic treatment duration in skin reconstruction with dermal substitutes is not well established. This study compares the incidence of infective complications after two different durations of perioperative antibiotic treatment in patients undergoing surgical reconstruction with skin dermal substitutes (SDS) after excision of skin cancer. Infective complications at the site of SDS were compared in subjects undergoing surgical reconstruction who received either a > 24‐hour (extended protocol) or a ≤ 24‐hour (short protocol) perioperative antibiotic treatment. Of 116 patients undergoing SDS surgical reconstruction, 62 (53.4%) received an extended schedule, and 54 (46.6%) received a short schedule. The two groups were similar for gender, age, comorbidities, American Society of Anesthesiologists score, and type of skin cancer. Overall incidence rate of infection was 20.7% (24/116). No differences in terms of risk of infection were observed between the two groups (OR: 1.04, 95% CI: 0.42‐2.55; P = .937). Patients undergoing SDS reconstruction in the limb/foot had a higher risk of infection in comparison with those undergoing SDS reconstruction in the chest/head (OR: 2.69, 95% CI: 1.06‐6.86; P = .038). The short protocol was demonstrated to be beneficial to patients undergoing surgical reconstruction with SDS. A ≤ 24‐hour perioperative antibiotic schedule did not increase the infection rate, potentially allowing a reduction of antibiotic exposure.